Cobalt plaque versus enucleation for uveal melanoma: comparison of survival rates. Issue 7 (July 1988) - Adams, K S; Abramson, D H; Ellsworth, R M; Haik, B G; Bedford, M; Packer, S; Seddon, J; Albert, D; Polivogianis, L
Abstract : Two hundred and twenty-three patients treated by cobalt plaque for uveal melanoma were compared with 416 patients treated by enucleation for uveal melanoma in terms of patient survival. The median follow-up time for the patients treated by cobalt plaque was 4.3 years. Kaplan-Meier survival curves were calculated up to five years following treatment based on time to tumour-related deaths. Cox's proportional hazards multivariate analysis was performed to determine which variables were related to melanoma-related deaths while controlling for age, size, and location of the tumours. Statistically significant predictive factors were location of tumour and largest tumour dimension. There was not a statistically significant difference in survival between patients treated by cobalt plaque and those treated by enucleation.